The Prices Analysis on the Real Estate Market (Research Bulletins of the Faculty of Economic Sciences, 2015)
This article has an empirical character and the main goal is the prices analysis on the real estate market in the city Koszalin with a particular attention to prices changes over time. The research problem was formulated as a following question: How strongly are residential property prices varied in Koszalin? In which period of time have been observed most of the sale transactions? What kind of real estate occurred in greatest demand?
Keywords: property; price; estate market